Anti-Islet Cell Antibody and Anti-ovarian Antibody Levels in Iraqi Women with Polycystic Ovary Syndrome (Medico Legal Update, 2021)
Objective: The objective of this analysis was to assess serum islet cell anti-bodies concentrations and antiovarian anti-bodies in the relationship between the PCOS patient and the stable control group.Material and Method: In this study, 250 Iraqi women aged between 20-50 years were studied. The patientswere divided into two groups: study group (n=125, PCOS women) and age-matched controls group (n=125normal women). The blood sample was obtained on the 2nd day of menstruation cycle. Islet cells Ab andanti ovarian Ab concentrations were determined in both groups.Results: Women with PCOS had higher serum islet cell concentrations higher than control levels (p < 0.05).The levels of islet cells Ab and Anti-ovarian Ab were substantially positively associated with BMI, highlevels of anti-mullerian hormone (AMH) and insulin resistance.Conclusion: The evidence from this study indicated that serum Islet cells Ab and anti-ovarian Ab levels inwomen with PCOS were observed to be higher compared with controls. Elevated serum Islet cells Ab andanti-ovarian Ab levels can be associated with high AMH and insulin resistance.Keywords: Islet cells, anti-ovarian Ab, anti-mullerian hormone, body mass index, polycystic ovarysyndrome.